Return of Syrians: Myth or Reality - Teke Lloyd, Armagan; Aksu Kargin, Inci; Kurtoglu, Ayca; Sirkeci, Ibrahim (Border Crossing, 2025)
The Syrian civil war, which began in 2011, has resulted in one of the largest refugee crises since World War II, displacing millions of Syrians both internally and internationally. Türkiye, which hosts over 3 million Syrian refugees, has become a focal point for discussions on refugee return and integration. With the collapse of the Ba'athist regime in December 2024 and the rise of Hay'at Tahrir al-Sham (HTS), the question of whether Syrian refugees will return to their homeland or remain in Türkiye has gained urgency. This paper employs the Conflict Model of Migration to analyze the physical, political, legal, economic, and social conditions influencing Syrian refugees' decisions to return or stay. The study argues that refugees' perceptions of human security in both Türkiye and Syria play a critical role in shaping their migration choices. While Türkiye offers relative stability and access to basic services, ongoing political instability, economic devastation, and social fragmentation in Syria create significant barriers to return. The paper concludes that, in the short to medium term, most Syrian refugees are likely to remain in Türkiye due to the perceived insecurities in their home country. However, the Turkish government's efforts to facilitate repatriation, coupled with international support, may influence future return dynamics. This study contributes to broader discussions on refugee crises, integration policies, and the long-term implications of mass displacement.